Pengembangan Produksi Abon Ikan di Desa Pasuruhan Kecamatan Kayen Kabupaten Pati - Hera Setiawan; Qomaruddin; Slamet Khoeron; sigit arrohman; Rochmad Winarso; Heru Saputro (Jurnal Inovasi Pengabdian Masyarakat, 2024)
The partner for this service activity is the MSME "Nuknan" located in Pasuruhan Village, Kayen District, Pati Regency. This MSME has been established since 2020 producing fish floss by employing 2 workers. The production of making fish floss is an alternative development of the oyster mushroom product processing business which has been developed previously. The obstacles experienced by MSMEs are that the process of making fish floss in MSMEs is still simple with some equipment that is still manual so the production capacity is low, the packaging process is carried out in MSMEs. This is still simple, and the process of selling products from MSMEs is still carried out traditionally. The solutions that have been carried out in this service activity include socializing and implementing technology for making shredded meat without oil, implementing Appropriate Technology (TTG) for mechanical system frying machines, improving design and packaging processes that are more market oriented, organizing training and marketing assistance through online marketing and organizing training and assistance in the promotional media design process through Canva. After completing the program there was an increase in achievement indicators such as all fish floss products produced were more hygienic (without oil), production capacity increased by 100%, all products were packaged with attractive designs and were market oriented, there was an increase in the number of sales by 70%, and there was an increase in income of 90%